Perlindungan Hukum atas Hak Anak yang Dieksploitasi sebagai Pengemis - Kusumawati, Dwi; Luluardi, Yunas Derta (Sharia Faculty, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study aims to examine the legal protection of children's rights exploited as beggars in Pekalongan Regency. The background of this research is the increasing phenomenon of child exploitation as beggars, which contradicts the children's rights stipulated in the constitution and laws. This research uses empirical juridical methods with legislative, conceptual, and qualitative approaches. Data were collected through observation, interviews, and documentation with informants from the Social Service as well as beggars and their children. The research results show that the legal protection efforts carried out by the Pekalongan Regency Government are still limited to handling and there are no specific basic regulations regarding the protection of children exploited as beggars. The existing policies only cover enforcement, rehabilitation, guidance, and social assistance, but have not provided strict legal protection against child exploitation. Moreover, the implementation of social assistance is often ineffective due to the lack of proper utilization by parents. This research contributes to a deeper understanding of the condition of legal protection for children exploited as beggars and provides recommendations for developing more specific and stringent regional regulations. The proposed recommendations include drafting regional regulations governing legal protection for exploited children, as well as increasing awareness and education for the community about the importance of children's rights and efforts to prevent child exploitation. This study also emphasizes the need for coordination between various government and non-governmental agencies to ensure effective and sustainable legal protection for children in Pekalongan Regency.